2022
DOI: 10.3389/fcimb.2022.1039811
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged mask wearing does not alter the oral microbiome, salivary flow rate or gingival health status – A pilot study

Abstract: The COVID-19 pandemic has resulted in the widespread use of N95 respirators and surgical masks, with anecdotal reports among healthcare providers and the public of xerostomia, halitosis, and gingivitis, a consortium of symptoms colloquially termed “mask mouth”. However, this has not been scientifically verified. The aim of this study was to assess changes in salivary flow rate, gingival health status and oral microbiome associated with prolonged mask use. A total of 25 dental students (mean age = 26.36 ± 1.58)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Interestingly, the presence or absence of xerostomia had no impact on the profile of the oral microbiome on the inside of the mask. A recent study on the mask microbiome conducted on dental students reported that the severity of xerostomia was not significantly related to mask wearing time (16). Lin et al reported that P. gingivalis and F. nucleatum were clearly associated with xerostomia after radioiodine therapy (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the presence or absence of xerostomia had no impact on the profile of the oral microbiome on the inside of the mask. A recent study on the mask microbiome conducted on dental students reported that the severity of xerostomia was not significantly related to mask wearing time (16). Lin et al reported that P. gingivalis and F. nucleatum were clearly associated with xerostomia after radioiodine therapy (30).…”
Section: Discussionmentioning
confidence: 99%
“…To date, few significant studies on masks and the attendant microbiome have been published. A study conducted by Au et al in 2022 reported that continuously wearing a mask for 2 months did not significantly change the salivary oral microbiome compared to those with minimal mask use (16). However, only the saliva microbiome but not the oral microbiome inside the mask was directly investigated, and the participants were limited to young dental students with an average age of 26.36 ± 1.58 years (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral-derived anaerobes can proliferate in chambers confined by face masks. Although the proliferation of microorganisms was observed on the inner surface of the mask, the amount of microbiome and VSC level did not significantly increase as the mask wearing time increased (33,36). Additional research is needed to scientifically investigate whether wearing a mask in turn increases microorganisms and VSC levels.…”
Section: Oral Causes Of Halitosismentioning
confidence: 99%
“…Anecdotal reports have suggested that subjective sensation of mouth dryness is attributed to the prolonged mask wearing due to the COVID-19 pandemic. According to a recent assessment of changes in salivary secretion and oral conditions, however, there is no evidence that mask wearing affects the flow rate of unstimulated whole saliva [120]. In addition to head and neck radiotherapy for cancer patients and autoimmune disorders like Sjögren's syndrome, certain medications are related to reduction of salivary secretion.…”
Section: Treatments Of Covid-19-associated Saliva Secretory Disordersmentioning
confidence: 99%